Improving the success and effectiveness of software developer training - Aitken, Ashley (Digital Ecosystems and Business Intelligence Institute, 2008)
Keeping software developers up-to-date with the latest technologies, methods, and tools, and training new developers on the fundamentals of software development is an important task for managers of software developers and the software developers themselves. The planning and choice of what training courses to take, when to take them, and how to take them, is much more important than just "using up an annual training budget." This experience report explains what the author (a trainer with over seventeen years exerience) has seen that does work and what doesn't work with regards to getting software developers trained (and keeping them trained). this report will suggest what trainng managers and software developers should do (and what they shouldn't do) to improve the success and effectiveness of their training and to ge the most from their training budget. It considers, for example, just-in-time and just-enough training, intensive versus extended training, and many other aspects of instructor-led training (including the responsibilities of those attending the training before, during, and after the training sessions).